Automation and Work Engagement: The Role of Job Insecurity, Self-Efficacy, and Career Transition Benefit - Wishnumurti, Aditya; Era Effendi, Danil Firdian; Juli Setiadi , Nugroho (Syntax Literate, 2026)
Automation is increasingly changing how organizations operate—not only by improving efficiency but also by reshaping job roles and responsibilities. While technological advancement can strengthen competitiveness, it may also create uncertainty about the future of certain positions. In such situations, maintaining employee engagement becomes more complex. This study explores how job insecurity and self-efficacy influence work engagement and examines whether career transition benefits play a moderating role among employees experiencing automation-driven changes in their workplaces. A quantitative cross-sectional approach was applied, involving 114 non-managerial employees. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that job insecurity significantly reduces work engagement, indicating that when employees feel uncertain about job continuity, their psychological involvement declines. Self-efficacy, however, does not show a significant effect, and career transition benefits do not moderate the relationships examined. These findings suggest that during automation-driven transformation, perceptions of job stability have a stronger influence on engagement than personal confidence or perceived career mobility opportunities.